Studying physics during the COVID-19 pandemic: Student assessments of learning achievement, perceived effectiveness of online recitations, and online laboratories - P. Klein; L. Ivanjek; M. N. Dahlkemper; K. Jeličić; M.-A. Geyer; S. Küchemann; A. Susac (Physical Review Physics Education Research, 2021)
The COVID-19 pandemic has significantly affected the education system worldwide, which was forced to respond with a sudden shift to distance learning. While successful distance teaching requires careful thinking, planning, and the development of technological and human resources, there was no time for preparation in the current situation. Various physics courses, including lectures, tutorials, and laboratory courses, had to be transferred to online formats, resulting in a variety of simultaneous, asynchronous, and mixed activities. To investigate how physics students perceived the sudden shift to online learning, we developed a questionnaire and gathered data from N=578 physics students from five universities in Germany, Austria, and Croatia. In this article, we report how the problem-solving sessions (recitations) and laboratories were adapted, how students judge the different formats of the courses, and how useful and effective they perceived them. The results are correlated with the students’ self-efficacy ratings and other behavioral measures (such as self-regulated learning skills). This study is descriptive in nature, and a survey study design was implemented to examine the relationships among the variables. We found that good communication abilities (r=0.48, p<0.001) and self-organization skills (r=0.63, p<0.001) are positively correlated with perceived learning achievement. Furthermore, the previous duration of studies had a significant impact on several self-reported achievement measures, resulting in consistently lower scores of students in their first academic year compared with students who were further along academically. We draw conclusions and suggest implications for future online classes on the instructor and faculty level. Suggestions include (i) focusing on first-year courses with on-campus teaching when facing limited lecture hall capacities, (ii) offering special courses for promoting self-regulated learning skills, (iii) emphasizing the positive aspects of distance learning, and (iv) installing networking services for supporting student communication.